The politicians’ responsibility in the Evangelium Vitae - Compagnoni, Francesco (Medicina e Morale, 1995)
The aim of this contribution is to demostrate that the Encyclical Evangelium Vitae's indications can be applied within politically democratic and ideologically pluralist societes. In order to do this, the way democracy works, from a legai point of view, is briefly analysed. The conclusion is that it is not the immediate popular consent and the direct social stimulus that are taken into account in the law. Moreover, the politician's conscience (which should pursue the common good) can not be neutralized when faced with public choices regarding life, in that these are only legitimate if they remain within the framework of the constitutional law and intemational treaties regarding man's rights. And besides, no political system can avoid being made legitimate through a series of values, even if only a small number, which are also a reference to the legitimacy of the ordinary law. The subject of life becomes vety controversial in politics if the foundation of man's rights and of the basic rights guaranteed by the constitution is not clear. There has to be a foundation, even if it is not the same one for everybody. In fact what is politically determining is the acceptance of the absoluteness of basic human rights. One of these is every person's right to life, before any legai decision or the recognition of any legislative institution. This is why modern law can not provide any legai legitimation for abortion, euthanasia and any other homicidial practice. It may not punish certain instances but it cannot recognize them directly because this area is not under its power. People and their rights logically come before social and state structures. Politicians, however, will only be able to realize ali this if honest people, the Catholics first of all, act within society above all to support life, whether beginning, threatened, in trouble or refused. Only by example it will be possible to create a welcoming society for every life, especially for the weakest life. We will then also have suitable legislative measures, obtained through the democratic parliamentary method.